1999
DOI: 10.1073/pnas.96.4.1732
|View full text |Cite
|
Sign up to set email alerts
|

Salt restriction induces pseudohypoaldosteronism type 1 in mice expressing low levels of the β-subunit of the amiloride-sensitive epithelial sodium channel

Abstract: The amiloride-sensitive epithelial sodium channel (ENaC) is a heteromultimer of three homologous subunits (␣-, ␤-, and ␥-subunits). To study the role of the ␤-subunit in vivo, we analyzed mice in which the ␤ENaC gene locus was disrupted. These mice showed low levels of ␤ENaC mRNA expression in kidney (Ϸ1%), lung (Ϸ1%), and colon (Ϸ4%). In homozygous mutant ␤ENaC mice, no ␤ENaC protein could be detected with immunof luorescent staining. At birth, there was a small delay in lung-liquid clearance that paralleled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 33 publications
7
109
2
1
Order By: Relevance
“…Knockout mice for all three ENaC subunits have been reported (11,36,46), and additional ENaC mutants have been studied (37,57). The most striking finding was that mutant newborns lacking the ␣-ENaC gene were unable to clear lung liquid from the alveolar spaces after birth ( Fig.…”
Section: Enac Transgenic Studiesmentioning
confidence: 93%
“…Knockout mice for all three ENaC subunits have been reported (11,36,46), and additional ENaC mutants have been studied (37,57). The most striking finding was that mutant newborns lacking the ␣-ENaC gene were unable to clear lung liquid from the alveolar spaces after birth ( Fig.…”
Section: Enac Transgenic Studiesmentioning
confidence: 93%
“…Indeed, such coupling was not observed in Sgk1 Ϫ/Ϫ , 17,37 AS Ϫ/Ϫ , 13 ␣ENaC( Ϫ/Ϫ )Tg, 38 and ␤ENaC m/m mice. 39 Although Sgk1 ϩ/ϩ and Sgk1 Ϫ/Ϫ mice did not display a significant difference in urinary Na ϩ excretion on a normal Na ϩ diet, their plasma [K ϩ ] was significantly different. 40 Morever, the significantly increased Na ϩ excretion was not coupled with markedly decreased K ϩ excretion and was instead paralleled by increased K ϩ excretion during the early phases of Na ϩ restriction in Sgk1 Ϫ/Ϫ versus Sgk1 ϩ/ϩ mice.…”
Section: High Dietary Potassium Attenuated the Effect Of Af17mentioning
confidence: 99%
“…38 Similarly, significantly elevated urinary [Na ϩ ]/[creatinine] and plasma [K ϩ ] in ␤ENaC m/m mice on a low Na ϩ diet were not accompanied with the expected changes in the urinary excretion of Na ϩ , K ϩ , and plasma [Na ϩ ]. 39 The most striking feature differing Af17 Ϫ/Ϫ from others identifiedthusfarliesinitsresponsetoaldo.Therenalphysiologyand BP phenotype in Af17 Ϫ/Ϫ mice is [aldo] dependent. Nevethereless, dramaticallyelevatedplasma[aldo]canrescueneithertherenalphysiology and BP phenotype of Sgk1 Ϫ/Ϫ nor the salt wasting of MR Ϫ/Ϫ mice.…”
Section: High Dietary Potassium Attenuated the Effect Of Af17mentioning
confidence: 99%
“…Over the past years, we have generated an allelic series of mutations at the ENaC (Scnn1) gene loci showing that any modified expression the ENaC subunits may cause a kidney disease [4,36,39,74,76,111]. Constitutive gene inactivation of all three subunits revealed that the absolute ENaC expression is essential for survival [4,35,59].…”
Section: Mouse Models For Kidney Diseasesmentioning
confidence: 99%
“…Various mouse lines have been generated in which the ENaC activity ranges from hypoactive channels (5-15% of total ENaC activity) to hyperactive channels (>150% of total ENaC activity; for review, see [37]. Reduced ENaC activity in mice bearing ENaC mutations led to clinical symptoms similar to PHA-1 (pseudohypoaldosteronism type 1) ranging from mild (e.g., mutation in the ßENaC gene locus [74]) to severe phenotype (e.g., γENaC knockout mice [4]). We further introduced one of the classical Liddle mutations (R566STOP) into the mouse ßENaC (Scnn1b) gene locus, thereby generating mice, which reproduce to a large extent the clinical symptoms of Liddle patients [76].…”
Section: Mouse Models For Kidney Diseasesmentioning
confidence: 99%